Classification of Cardiac Arrhythmia using ID3 Classifier Based on Wavelet Transform - Sadiq, Ahmed; Shukr, Nidhal (Iraqi Journal of Science, 2024)
Accurate detection of Electro Cardio Graphic (ECG) features is an important demand for medical purposes, therefore an accurate algorithm is required to detect these features. This paper proposes an approach to classify the cardiac arrhythmia from a normal ECG signal based on wavelet decomposition and ID3 classification algorithm. First, ECG signals are denoised using the Discrete Wavelet Transform (DWT) and the second step is extract the ECG features from the processed signal. Interactive Dichotomizer 3 (ID3) algorithm is applied to classify the different arrhythmias including normal case. Massachusetts Institute of Technology-Beth Israel Hospital (MIT-BIH) Arrhythmia Database is used to evaluate the ID3 algorithm. The experimental result shows that the accuracy of ID3 is 92% in the case of Haar transform and 94% with Daubeshies4 transform.